2017
DOI: 10.1017/s1368980017000635
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in meal patterns and timing with regard to central obesity in the ANIBES (‘Anthropometric data, macronutrients and micronutrients intake, practice of physical activity, socioeconomic data and lifestyles in Spain’) Study

Abstract: ObjectiveTo study the association of meal patterns and timing with central obesity to identify the best dietary strategies to deal with the increasing obesity prevalence.DesignA cross-sectional study performed on data from a representative sample of the Spanish population. Height and waist circumference were measured using standardized procedures and waist-to-height ratio (WHtR) was calculated. The sample was divided into those without central obesity (WHtR<0·5) and those with central obesity (WHtR≥0·5).Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
(92 reference statements)
1
13
0
2
Order By: Relevance
“…Our findings are consistent with some [4,5,6,26], but not all [27,28], studies noting associations between increased snack frequency and obesity among adults. Our findings are also consistent with others noting positive relationships between evening snacking and obesity [6,9,26] as well as negative relationships between morning and mid-day snacking and obesity [29]. These findings are supported by studies that have noted higher energy-density of snacks overall among U.S. adults [30] as well as higher energy-density of evening snacks and lower energy-density of morning snacks among French adults [31].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with some [4,5,6,26], but not all [27,28], studies noting associations between increased snack frequency and obesity among adults. Our findings are also consistent with others noting positive relationships between evening snacking and obesity [6,9,26] as well as negative relationships between morning and mid-day snacking and obesity [29]. These findings are supported by studies that have noted higher energy-density of snacks overall among U.S. adults [30] as well as higher energy-density of evening snacks and lower energy-density of morning snacks among French adults [31].…”
Section: Discussionsupporting
confidence: 93%
“…2,35 Further, in both lean and obese people, frequent snacking may lead to slower weight loss or even weight gain. 36 This study revealed that the proportion of medical students who consumed vegetables and fruits daily was 20.4% and 11.9%, respectively. A prior study conducted in Saudi Arabia among university students showed that 22% of them consumed at least five servings of vegetables per day.…”
Section: Discussionmentioning
confidence: 83%
“…In our survey, breakfast brought 22% of total energy intake among regular breakfast eaters, and 18% among all survey participants, including occasional breakfast eaters. This proportion is slightly higher than in other western high-income countries: e.g., 14% in the Netherlands [ 49 ], 15% in Britain [ 50 ], 15% in the U.S. [ 15 ], 17% in France [ 51 ], or 16% in Spain [ 52 ]. This may represent different eating habits in the distribution of daily food consumption occasions, the proportion of breakfast skippers, and/or the definition of breakfast.…”
Section: Discussionmentioning
confidence: 99%